21st AIAA Computational Fluid Dynamics Conference 2013
DOI: 10.2514/6.2013-3066
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Discontinuous Galerkin Method for Compressible Turbulence

Abstract: In the present study, a discontinuous Galerkin (DG) framework is developed to simulate chemically reacting flows. The algorithm combines a double-flux method to account for variable thermodynamic properties, a Strang-splitting scheme for the stiff reaction chemistry, a robust WENO-based shock limiter, and the non-linear viscous-diffusive transport is discretized using the BR2 method. The algorithm is verified and validated by considering a series of one-and two-dimensional test cases, and results are compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The reader is referred to past work on this topic for additional information. 12,13 A. Combining DG and MUSCL Using Recovery for the diffusive terms, accuracy of the order 3p + 2 in the cell-average of the conservative quantities are readily achieved by using information from the neighboring cells.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The reader is referred to past work on this topic for additional information. 12,13 A. Combining DG and MUSCL Using Recovery for the diffusive terms, accuracy of the order 3p + 2 in the cell-average of the conservative quantities are readily achieved by using information from the neighboring cells.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…12,13 While the temporal evolution of the kinetic energy and enstrophy were well-resolved on grids of 64 3 , that dilatation was not, particuarly in the more compressible simulations. It is suspected that lower accuracy of the advection scheme is responsible for this phenomenon.…”
Section: Introductionmentioning
confidence: 97%
“…3 Compared to other DG modifications for handling parabolic/elliptic PDE behavior, RDG is characterized by extremely high order of accuracy, high computational cost per iteration, and a specialized boundary treatment to maintain high order accuracy. The general concept of Recovery has assisted in the development of similar schemes, for example the reconstruction-based DG method of Luo et al 4 Additionally, Recovery DG has been shown to competent in Direct Numerical Simulation (DNS) of compressible turbulence with periodic boundary conditions by Johnsen et al 5,6 . However, the Recoverybased DG method as developed by Lo and Van Leer, despite its promise, has been sparsely applied to real flow physics problems.…”
Section: Introductionmentioning
confidence: 99%
“…2 Compared to other DG approaches for handling parabolic/elliptic PDEs, Recovery DG is characterized by high order of accuracy, small spectral radius, and no ambiguously bounded stabilization parameters. The general concept of recovery has assisted in the development of similar schemes, for example the reconstruction-based DG method of Luo et al, 3 the enhanced stability recovery scheme of Ferrero et al, 4 and the modified recovery scheme (MRDG-1x) of French et al 5 Additionally, Recovery DG has demonstrated competence when applied to the viscous fluxes of the compressible Navier-Stokes equations in Direct Numerical Simulation of compressible turbulence by Johnsen et al 6,7 For a given interface in the computational domain, the recovery process builds a smooth polynomial function (the "recovered" solution) across the union of the neighboring elements, maximizing the use of the solution data associated with each element and providing an unambiguous and accurate approximation for both the solution and its gradient along the interface. The effect of the recovery procedure is demonstrated work will always be referred to as exp(y), and the lowercase e is reserved to refer to element addresses.…”
Section: Introductionmentioning
confidence: 99%